Fire and development influences on sagebrush community plant groups across a climate gradient in northern Nevada. Issue 12 (17th December 2019) - Wood, David J. A.; Seipel, Tim; Irvine, Kathryn M.; Rew, Lisa J.; Stoy, Paul C.
Abstract: The sagebrush biome covers much of the western United States yet is at risk from ongoing disturbances. Physical disturbances such as fire often overcome the resistance of sagebrush communities to biological disturbances such as invasion by non‐native species, but the impact of burn severity or combined disturbance types on sagebrush community composition remains unclear. We examined the relationship between native functional groups and non‐native annual grass cover to the number of fires, burn severity, anthropogenic development, and vegetation treatments in northern Nevada, USA. We used Bureau of Land Management vegetation monitoring plots and existing climate, fire, and vegetation treatment databases to explore relationships using beta regression. After accounting for mean annual precipitation and temperature, and elevation, we quantified functional group mean cover related to levels of burn severity, numbers of fires, development, and vegetation treatments. Native herbaceous (grass and forb) groups were resilient to fire, but fire caused large declines in shrub and sagebrush cover. Non‐native annual grass cover was associated with higher burn severity and the first fire at a site. We did not find evidence that post‐fire restoration treatments were associated with increased native cover or decreased non‐native cover. However, shrub control and soil disturbing treatments (discing and chaining) were associated with decreased native perennial grass cover and increased non‐native annual grass cover. Functional groups displayed varying patterns related to anthropogenic development and fire. For example, development had a larger impact on non‐native cover at lower levels of burn severity, whereas forbs increased following fire only at lower levels of development. Although in some cases sagebrush communities showed resilience to disturbance, our results showed resistance to invasion by non‐native annual grasses can be overcome by combinations of disturbances at lower levels or by severe events.